2017
DOI: 10.1590/s0102-053620170222
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho agronômico de genótipos de alface americana no Submédio do Vale do São Francisco

Abstract: Agronomic performance of crisphead lettuce genotypes at Sub-Middle São Francisco ValleyAmong the types of lettuce currently cultivated, crisphead lettuce has exceeded, which aims to serve mainly the networks of fast food. In order to evaluate the productive behavior of lettuce cultivars in Sub-Middle of São Francisco Valley, Pernambuco State, Brazil, two experiments were carried out, in 2013 and 2014. Randomized blocks with twelve genotypes in 2013 and twenty-two genotypes in 2014, with three replications, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
(8 reference statements)
2
8
1
3
Order By: Relevance
“…These values are higher than what was observed for crisphead lettuce cultivars in Carcéres-MT, where yield indexes ranged from 15 to 27 t ha -1 with an average temperature of 29 °C (Neves et al, 2016) were verified. Meanwhile, Yuri et al (2017) found values above 40 t ha-1 in the region of Petrolina-PE, with an average temperature of 22 °C, with these results being higher than the ones from this research.…”
Section: /9contrasting
confidence: 90%
See 3 more Smart Citations
“…These values are higher than what was observed for crisphead lettuce cultivars in Carcéres-MT, where yield indexes ranged from 15 to 27 t ha -1 with an average temperature of 29 °C (Neves et al, 2016) were verified. Meanwhile, Yuri et al (2017) found values above 40 t ha-1 in the region of Petrolina-PE, with an average temperature of 22 °C, with these results being higher than the ones from this research.…”
Section: /9contrasting
confidence: 90%
“…The cultivar with the highest total fresh matter accumulation was Balsamo under chromatinet ® net with a mean value of 409.50 g plant -1 , and this same genotype had a 48% reduction in this variable when grown under full sun. Yuri et al (2017), for this same variety, observed values of 875 g plant -1 in the same region of the present research; probably the difference is due to the production periods of that study, which had mild temperatures, while this present research was conducted in high temperatures.…”
Section: Resultssupporting
confidence: 48%
See 2 more Smart Citations
“…A alfacicultura em muitas regiões é prejudicada devido às intempéries do clima, o que pode reduzir a oferta do produto afetando a regularidade de oferta do produto durante todo o período do ano, assim o cultivo protegido é uma importante alternativa que pode garantir a oferta do produto quando as variações climáticas não favorecem o cultivo convencional (VALERIANO et al, 2016). A alta sensibilidade as condições adversas de temperatura, umidade e precipitação são consideradas a principal limitação desta cultura (YURI et al, 2017).…”
unclassified